The longitudinal influence of narcissism in the team context. Issue 2 (1st March 2015) - Felty, Ryan; Whitaker, Brian G.; Bergman, Shawn M.; Bergman, Jacqueline Z.
Abstract : The current study integrates self-enhancement and social exchange theories to construct hypotheses in which team-level narcissism is expected to negatively influence team-level task performance ratings and team-level organizational citizenship behaviors directed at team members (OCB-Is). Additionally, individual-level narcissism is expected to negatively influence peer performance ratings. Based on longitudinal data collected from 89 study participants constituting 29 project teams, results indicate (a) team-level narcissism influences task performance, (b) team-level narcissism influences changes in OCB-Is over time, and (c) individual-level narcissism influences peer performance ratings. Our findings suggest the necessity for practitioners to consider individual differences in the strategic formation of work groups.